Benefits and barriers to participation in colorectal cancer screening: a protocol for a systematic review and synthesis of qualitative studies. Issue 2 (27th February 2014) - Honein-AbouHaidar, Gladys N; Kastner, Monika; Vuong, Vincent; Perrier, Laure; Rabeneck, Linda; Tinmouth, Jill; Straus, Sharon; Baxter, Nancy N
Abstract : Introduction: Colorectal cancer (CRC) poses a serious health problem worldwide. While screening is effective in reducing CRC mortality, participation in screening tests is generally suboptimal and social inequities in participation are frequently reported. The goal of this review is to synthesise factors that influence an individual's decision to participate in CRC screening, and to explore how those factors vary by sex, ethnicity and socioeconomic status. Data sources: A primary search of Cumulative Index to Nursing and Allied Health Literature (CINAHL), MEDLINE, EMBASE, PsycINFO, and a secondary search of grey literature and articles taken from references of included articles (from inception to July 2013). Design: A systematic review and Meta-study synthesis of qualitative studies that address perceived benefits and barriers to participation in CRC screening tests among adults 50 years of age or older. Review methods: The two-staged Meta-study methodology by Paterson will be used to conduct this review. In stage 1, similarities/differences, patterns and themes will be identified across three levels of analysis while preserving the context of original studies. In stage 2, synthesis will extend beyond the analysis to generate new theory of the phenomenon through a process called Meta-synthesis. Discussion: This review offers to generate a framework to better understand benefits and barriers that affect decision-making to participate in CRC screening among different sectors of the population. This framework will be a relevant tool for policy makers in framing educational materials, for patient-centered communication, and for researchers interested in the science of equity. This review is registered in PROSPERO (registration number: CRD42013005025).